Developments in source monitoring and linguistic encoding of source - Ögel, Hale. (Thesis (M.A.)-Bogazici University. Institute for Graduate Studies in the Social Sciences, 2007., 2007)
The present study examined Turkish-speaking children’s source monitoring ability, and whether their ability to use evidentiality markers predicts their source monitoring abilities. Eighty-seven 3- to 6-year-old children participated over two sessions in two source monitoring tasks, (1) Mode of Knowledge Access Task, and (2) Source Identification Task; and three linguistic tasks, (1) Direct Experience Task, (2) Inferential (-mIs) Task, and (3) Reportative (-(I)mIs) Task. In the immediate part of the Mode of Knowledge Access Task, 3-year-olds performed worse than older children. In the delayed part of this task, 3-year-olds’ performance was lower than that of 6-year-olds. Identification of linguistic report was found to be more difficult than identification of other sources. On the Source Identification Task, 3-year-olds gave less correct responses, made more errors than 5- and 6-year-olds. All age groups’ source responses were found to differ depending on the source. These findings support the hypothesis that children’s source monitoring ability increases with age. The second hypothesis that children’s ability to use evidentiality markers to report indirect experience increases with age was also supported. On the Reportative Task, 3- and 4-year-olds performed worse than 5- and 6-year-olds, and on the Inferential Task, 3-year-olds performed worse than 6-year-olds. iv The last hypothesis that children’s performance on the linguistic tasks would predict their performance on the source monitoring tasks was partially supported. Performance on the Reportative Task was found to predict performance on the Source Identification Task. Discussion of findings focuses on different definitions of source monitoring and relations between language and cognition.
Keywords: Memory in children.; Cognition in children.